ETHNOMATHEMATICS WAT HUA LAMPHONG TEMPLE - Andino Maseleno; Tri Susilowati; Rahul Chauhan (Hipotenusa Journal of Research Mathematics Education (HJRME), 2024)
In Thailand alone there are more than 35,000 temples, ranging in size from magnificent to simple. One of them is the prominent temple in Bangkok, Wat Hua Lamphong. Wat hua Lamphong is a Royal Buddhist temple, classified as third-class, located in Bangkok's Bang Rak District, Thailand. Located on Jalan Rama IV, it functions centers for spiritual guidance, education, and community activities.The purpose of this study is to describe the results of mathematical exploration as a cultural product through the ethnomathematical bridge to Wat hua Lamphong Temple. The results of this research are presented in a qualitative form with an ethnographic approach that describes the history, as well as the philosophy and structure of the building and ornament of Wat hua Lamphong Temple. Data sources were obtained through literature studies, interviews, observations, and documentation. The results of the study show that (1) Wat Hua Lamphong Temple has several aspects of mathematics in geometry material. Build such as triangles, trapezoids, prisms, circles and build spaces such as bowed cones and geometry of reflection transformation, translation and dilation. Not only geometric shapes, other aspects are also seen in the triangle of the building, two lines that are parallel to each other and the integral volume of the rotating object, (2) Overall, the exploration of mathematics and culture through ethnomathematics not only enriches the learning experience but also fosters a deeper appreciation of the cultural dimension of mathematical knowledge.